Portal cholangiopathy secondary to cavernomatous transformation of the portal vein. Case report - Karla J. Arroyo García; Luis A. Esquivel-Pacheco; Alexis V. Hinostroza-Pezo; Adolfo Gamiño-Morfín; Alejandro D. Mendoza-Rea; Luis R. Alvarez-Martín; Carlos A. Galvan-Castro (Annals of Hepatology)
Introduction and Objectives: Portal cholangitis is a set of alterations that appear in the bile duct secondary to portal hypertension (PH). It is extremely rare and its main etiology is cavernomatous transformation of the portal vein (CPVT). The objective is to present the case of a patient with portal cholangiopathy secondary to TCVP. Materials and Patients: A 17-year-old man with no relevant history began with hemorrhoidal bleeding, requiring hemorrhoidectomy. After 3 weeks, he presented abdominal pain and constipation. Abdominal computed tomography revealed free abdominal fluid, splenomegaly, and portal dilation. A diagnostic paracentesis was performed with GASA 3.1 and liver Doppler ultrasound with a 9mm portal vein, collateral veins, thrombosis and portal cavernomatosis. Initial endoscopy showed small esophageal varices. Hepatotropic infections, HIV and thrombophilias were ruled out, concluding prehepatic PH secondary to TCVP and Child-Pugh A chronic liver disease (CLD).At 3 years of follow-up, jaundice, generalized pruritus, direct hyperbilirubinemia asadded, with CA 19.9, normal IgG, negative ANA and AMA, and cholangio resonance with stenosis of the common bile duct and dilation of the intrahepatic and extrahepatic bile ducts.In 2023, at 24 years of age, he had advanced decompensated CLD secondary to probable portal cholangiopathy due to TCVP, with persistent ascites, large esophageal varices, encephalopathy and recurrent cholangitis, so it was decided to place percutaneous drainage with biochemical improvement but presenting new episode of severe acute cholangitis associated with septic shock and acute-on-chronic liver failure, with a torpid evolution despite management with meropenem and ceftriaxone. Results: TCVP is characterized by the formation of dilated collateral venous pathways in the portal vein, secondary to portal thrombosis, causing PH. A rare complication of both is portal cholangiopathy.In the clinical case presented, what is notable is the patient's evolution characterized by cholestasis and CLD secondary to cavernomatosis due to portal thrombosis of unknown cause with progression of complications derived from portal hypertension. As part of the approach, hepatic infectious and hepatic autoimmune processes are ruled out and CA 19.9 is requested to assess the risk of cholangiocarcinoma. Subsequently, a magnetic resonance cholangiography was performed which showed a stenosis of the common bile duct.Therefore, a portal cholangiopathy was considered due to the history of TCVP and the clinical, biochemical and imaging data that supported the diagnosis despite its low frequency. There are various theories about PH and its involvement of the bile duct, but it is considered to be due to compression of the bile duct walls secondary to the cavernoma, dilation of the venous plexuses of the common bile duct and ischemia, the latter being the reason for the failure. of bile duct diversion in some patients, as in this case presented. Conclusions: Portal cholangiopathy should be considered in patients with cholestasis and portal hypertension; its origin should also be investigated in order to provide timely management that reduces the risk of complications and disease progression.